Educating for Biocultural Diversity and Sustainable Development in First Years of Schooling: An Analysis of Documents From the Portuguese Educational System - Batista, Bruna Fonseca; Andrade, Ana Isabel (Frontiers in Education, 2021)
Educating for sustainable development can encompass different perspectives and possibilities that allow attaining the goals of more sustainable development, as predicted by the United Nations for 2030. This type of education also involves a humanist and citizenship education, which can prepare children, youth, and adults to face current and future challenges, local and global, as actors in building a better future. We believe, however, that for education to bear fruit, it is important that children, from the first years of schooling, can be in contact with different perspectives, people, ways of learning and worldviews, in an education locally contextualized and relevant, with high links with the natural and social environment involving the communities. An education that values linguistic and cultural diversity, without forgetting biodiversity and the influences they exert on the education of an individual, both personally and socially, and, simultaneously, in the construction of a community with its specific culture. As such, looking at an education that encompasses the relationships between linguistic, cultural, and biological diversity, the present study wants to understand how biocultural diversity is present in the normative-legal documents that govern education for the first years of schooling in the Portuguese educational system and, above all, if its existence is considered in education for sustainable development. For this study, seven documents were analyzed, and the results demonstrate a gap regarding the presence of biocultural diversity in those that are guiding documents for the first years of schooling in Portugal, which refers to an incomplete perspective of education for sustainable development, forgetting languages, cultures, and subjects.